Children's meaning-making choices in EFL writing: The use of cohesive devices and interpersonal resources. (October 2019) - Yasuda, Sachiko
Abstract: Previous research has addressed L2 writing development in relation to form (e.g., complexity, accuracy, fluency) and holistic measures. Despite the academic interest in these formal and global features, however, researchers have been dissatisfied with the measurements that typically assess writing through quantitative criteria (e.g., Ortega, 2015 ). What is needed is not mere numbers, but something far richer that can explain what exactly each number means in terms of writers' meaning-making attempts. This study thus aims to describe how young writers use cohesive devices and different interpersonal resources to engage the reader. The participants were Grade 5 students at a Japanese elementary school, and they came from different instructional settings: students who learn English in a Content Language Integrated Learning (CLIL) environment, and those who learn English in an EFL-only setting. The results showed that although group differences were identified between CLIL and EFL-only students in terms of formal and global features, commonalities were also detected in some of their meaning-making choices. The results imply the importance of examining the writing development of EFL writers based on what they can do in terms of meaning making, rather than based on what they cannot do in terms of form alone.